The Integration of Young Third-country Nationals into Educational Setting of Latvia - Pičukāne, Ērika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The integration of children of Third-country nationals into the society and labour market is one of the hot issues in Latvian education, therefore it is important to summarize and spread the professional experience of teachers working with these children.The education is the main tool to turn them into creative and successful members of Latvian society. In other words, migration can be useful to both migrants and the host country.There is an extremely high demand for specialists capable of working with migrants' children of different ethnicities, mother tongues, cultural backgrounds as well as knowledge levels that may be challenging because of a mismatch of education standards in Latvia and their home countries.